1971
DOI: 10.1128/am.21.3.527-533.1971
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Streptomyces Spore Surfaces into Five Groups

Abstract: Streptomyces spores surfaces have been classified into five groups, smooth, warty, spiny, hairy, and rugose, by examination of carbon replicas of spores with the transmission electron microscope and by direct examination of spores with the scanning electron microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The study of macro-morphological characteristics showed that this isolate belongs to the series of gray, this color is specific to bacteria of the genus Streptomyces (Tresner and Backus 1963). The micro-morphological characterization showed that the isolate exhibits smooth spores, and spiral type and straight to flexuous that are typical of the genus Streptomyces (Dietz and Mathews 1971). Physiologically, the isolated strain was metabolically active.…”
Section: Discussionmentioning
confidence: 87%
“…The study of macro-morphological characteristics showed that this isolate belongs to the series of gray, this color is specific to bacteria of the genus Streptomyces (Tresner and Backus 1963). The micro-morphological characterization showed that the isolate exhibits smooth spores, and spiral type and straight to flexuous that are typical of the genus Streptomyces (Dietz and Mathews 1971). Physiologically, the isolated strain was metabolically active.…”
Section: Discussionmentioning
confidence: 87%
“…Pure culture of each strain was inoculated in freshly ISP 2 broth and incubated at 28°C, 200 rpm for 2 days. The genomic DNA was extracted by physical and chemical combination methods (51). The 16S rRNA gene was amplified from the extracted genomic DNA by using the universal primers 1492R (5′ACGGCTACC TTGTTACGACTT 3′) and 27F (5′AGTTTGATCCTGGCTCAG 3′) directions.…”
Section: Genotypic Characteristics 16s Rrna Gene Sequencementioning
confidence: 99%